2009
DOI: 10.1111/j.1439-0272.1991.tb02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness mechanism of chlomipramine by neurophysiological tests in subjects with true premature ejaculation

Abstract: The effectiveness mechanism of the chlomipramine treatment was evaluated by sacral evoked response (SER) and dorsal nerve somatosensory cortical evoked potential (DN-SEP) testings in 15 patients with true premature ejaculation (TPE) . We couldn't demonstrate any significant difference between the values of either latency times or amplitudes of the evoked responses determined just before and at the end of the treatment with chlomipramine in these patients. However, the sensory thresholds were 24.4 * 4.3 V in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Treatment with daily fluoxetine or clomipramine in two independent studies showed significantly increased penile sensory thresholds in men with PE [9,10]. In both cases, there was no change in either the amplitude or latencies of sacral evoked response and cortical SEPs.…”
Section: Data From Clinical Trials Exploring Drug Treatmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…Treatment with daily fluoxetine or clomipramine in two independent studies showed significantly increased penile sensory thresholds in men with PE [9,10]. In both cases, there was no change in either the amplitude or latencies of sacral evoked response and cortical SEPs.…”
Section: Data From Clinical Trials Exploring Drug Treatmentsmentioning
confidence: 95%
“…The measurement of intravaginal ELT (IELT) in the male population shows a skewed distribution, and the question of where to apply a particular threshold that defines a particular IELT as being premature or not has been largely academic, as previous definitions of PE did not include such a threshold point. As a result, the population of men with PE in many clinical trials and neurobiological evaluations [9–11] have been largely self‐diagnosed, are somewhat heterogeneous and, in many cases, poorly defined, making comparative evaluations difficult.…”
Section: Aetiology Of Pementioning
confidence: 99%
“…Two findings of further interest have, however, resulted from this line of research: the use of topical anesthetic creams increases the latency of the SSEP wave in men with PE, indicating their direct effect on the penile sensory pathways [27,28]. In contrast, clomipramine does not affect SSEP latency or amplitude, thus supporting the idea that serotonin reuptake inhibitors exert their effects through central (rather than afferent spinal) mechanisms [29].…”
Section: Comment and Conclusionmentioning
confidence: 99%
“…because of the unclarified mechanism and systemic side effects. [5][6][7][8] Attempting to elucidate the etiologic bases of PE, we had investigated penile sensory threshold changes in patients with primary PE, and found that patients with PE…”
Section: The Bcrap Changesmentioning
confidence: 99%
“…[5][6][7][8] Recently, neurobiological studies have made it likely that PE is not only a psychological disorder but a neurobiological phenomenon.…”
Section: Introductionmentioning
confidence: 99%